2023
DOI: 10.3390/antibiotics12071105
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between COVID-19 and ICU-Acquired Bloodstream Infections Related to Multidrug-Resistant Bacteria

Antoine Piantoni,
Marion Houard,
Gaetan Piga
et al.

Abstract: A bloodstream infection (BSI) is a severe ICU-acquired infection. A growing proportion is caused by multidrug-resistant bacteria (MDRB). COVID-19 was reported to be associated with a high rate of secondary infections. However, there is a lack of data on the relationship between COVID-19 and the incidence of MDRB ICU-acquired BSI. The aim of this study was to evaluate the relationship between COVID-19 and ICU-acquired BSI related to MDRB. This retrospective study was conducted in a single-center ICU during a on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Regarding the incidence of BSI related to MDR bacteria, a retrospective monocentric study on 497 COVID-19 patients and 823 controls reported that COVID-19 patients had a higher incidence of BSI related to MDR bacteria [ 38 ] (adjusted cause-specific HR (cHR) 2.65, 95% CI 1.25–5.59, in line with the COVID-BMR study [ 37 ]). Similarly, a retrospective international study in 53 ICUs found an increased incidence of hospital-acquired BSI related to difficult-to-treat Gram-negative bacteria in COVID-19 ( n = 252) vs. controls ( n = 577; 19.4% vs. 13%, p = 0.017) [ 29 ].…”
Section: Epidemiologymentioning
confidence: 75%
See 3 more Smart Citations
“…Regarding the incidence of BSI related to MDR bacteria, a retrospective monocentric study on 497 COVID-19 patients and 823 controls reported that COVID-19 patients had a higher incidence of BSI related to MDR bacteria [ 38 ] (adjusted cause-specific HR (cHR) 2.65, 95% CI 1.25–5.59, in line with the COVID-BMR study [ 37 ]). Similarly, a retrospective international study in 53 ICUs found an increased incidence of hospital-acquired BSI related to difficult-to-treat Gram-negative bacteria in COVID-19 ( n = 252) vs. controls ( n = 577; 19.4% vs. 13%, p = 0.017) [ 29 ].…”
Section: Epidemiologymentioning
confidence: 75%
“…As presented in Table 1 , 24 studies providing estimates of the association between COVID-19 status and ICU-acquired infection/colonization with resistant bacteria fulfilled our inclusion criteria [ 2 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations